Epistemological Anarchism and Methodological Pluralism: Reassessing Paul Feyerabend’s Thought in Relation to Islamic Ijtihad - Efendi, Rifat Syauqi; Fanani, Ahmad Farid; Ramananda, Vici; Pradipta, Raihan (Islamic Thought Review, 2025)
This study aims to critically examine the relevance of Paul Feyerabend’s epistemological anarchism to the Islamic tradition of ijtihad, particularly in addressing methodological rigidity within contemporary Islamic scholarship. The increasing dominance of singular methodological frameworks in Islamic studies has contributed to epistemic stagnation and limited interpretive creativity. Employing a qualitative research design based on library research, this study analyzes Feyerabend’s major philosophical works alongside classical and contemporary Islamic epistemological sources. Using descriptive and comparative methods, the analysis explores conceptual convergences between Feyerabend’s critique of methodological absolutism—encapsulated in his principle of “anything goes”—and the inherently pluralistic nature of ijtihad as practiced by classical Muslim jurists. The findings demonstrate that both frameworks emphasize intellectual freedom, contextual reasoning, and the legitimacy of diverse methodological approaches in the pursuit of knowledge and truth. Rather than advocating epistemic relativism, the integration of Feyerabend’s insights with Islamic epistemology offers a model of methodological openness grounded in ethical responsibility and revelatory norms. This study argues that such an epistemological synthesis can contribute to the revitalization of ijtihad by promoting an inclusive, adaptive, and context-sensitive paradigm of Islamic knowledge production, capable of engaging constructively with modern scientific rationality while remaining faithful to the normative foundations of Islamic thought.